2004
DOI: 10.1071/fp04126
|View full text |Cite
|
Sign up to set email alerts
|

Planteose is a short-term storage carbohydrate in Actinidia leaves

Abstract: The polyol myo-inositol constitutes 10-20% of soluble carbohydrates in mature leaves of Actinidia deliciosa (A.Chev.) C.F. Liang et A.R. Ferguson var. deliciosa 'Hayward' and A. arguta (Sieb. et Zucc.) Planch. ex Miq. var. arguta. In contrast with other non-structural carbohydrates, myo-inositol concentrations in A. deliciosa leaves increase only slightly during development from sink to source, and are not affected in source leaves by increased sink demand upon fruit set. In mature fruit-bearing leaves myo-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Radiolabelled carbon was rapidly incorporated into planteose in the A. arguta leaf, showing it is a primary photosynthetic product that accumulates during the day and begins to decline in the evening and night, reaching low concentrations by dawn (Klages et al, 2004). Planteose has previously been reported as a storage carbohydrate in cyclamen leaves and petioles (Rothe et al, 1999) and in sesame seeds (Dey, 1980) but there was no evidence that it was translocated in either species.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Radiolabelled carbon was rapidly incorporated into planteose in the A. arguta leaf, showing it is a primary photosynthetic product that accumulates during the day and begins to decline in the evening and night, reaching low concentrations by dawn (Klages et al, 2004). Planteose has previously been reported as a storage carbohydrate in cyclamen leaves and petioles (Rothe et al, 1999) and in sesame seeds (Dey, 1980) but there was no evidence that it was translocated in either species.…”
Section: Introductionmentioning
confidence: 97%
“…In A. arguta, sucrose and planteose are the major sugars found in the leaves (Klages et al, 2004). Radiolabelled carbon was rapidly incorporated into planteose in the A. arguta leaf, showing it is a primary photosynthetic product that accumulates during the day and begins to decline in the evening and night, reaching low concentrations by dawn (Klages et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factor conferring mobility to boron in the phloem is the synthesis of sugar-alcohols and the subsequent transportation of B-poliol complexes. On the other hand, Bieleski et al (1997) mentioned that Actinidia plants contain unusually high levels of inositol, and Klages et al (2004) indicated the possibility that this sugar might be transported by the phloem from the leaves to the fruits, forming B-inositol complexes that may allow boron mobility. Therefore, boron may accrue in the meristematic zones in fruits of A. deliciosa.…”
Section: Boron Dynamics In Kiwifruit (Experiments 2)mentioning
confidence: 99%
“…In addition, Klages et al (2004) found that mioinositol represents between 10 and 20% of the soluble carbohydrates in the mature leaves of A. deliciosa, cv. Hayward.…”
Section: Introductionmentioning
confidence: 99%